TEACHING ENGLISH IN SECONDARY SCHOOL: APPROACHES, METHODS, AND TECHNIQUES - Nasrullah Nasrullah; Elsa Rosalina; Fatchul Mu’in (Politeknik Negeri Bengkalis, 2021)
Teaching English in secondary schools is important to give primary knowledge of English to students. Teachers need to know what the students are needed in learning English so that teachers can apply appropriate techniques in teaching. Yet, since this is the era of industrial revolution 4.0, many teachers are still blurred with beliefs and principles of language teaching so that teachers’ intervention in providing the fruitful materials and the novel techniques are usually scarcely to be found in their instruction. This study is aimed to describe the approaches, methods, and techniques applied by teachers of secondary schools in Tanjung, Tabalong when teaching English in class. This study employed qualitative case study methodology which produces descriptive data. There were 30 teachers as the participants in this research. The data were collected by using interview and a questionnaire. The result of the research shows that even some of the teachers are using materials outside of the textbook, methods and techniques of teaching English in secondary schools still do not based on demanded approaches so that the face of English teaching has the struggling to find its look in pursuing the goal of communicative competence.